Estudio in vivo de hidrogeles a base de submucosa intestinal porcina y quitosano como apósitos regenerativos de heridas profundas (2018)
Skin wounds are a major public health problem, representing an annual approximate cost of 25 billion dollars in the USA. This is rapidly growing problem due to risk factors such as diabetes, obesity and aging population. Current solutions cannot satisfactorily solve this problem, because they did not promote regeneration or are limited by healthy skin availability, so we propose a Small Intestinal Submucosa-Chitosan (SIS/Ch) hydrogel as a deep wound healing cost/effective material with hemostatic, angiogenic and reepithelization capacities. The objective of this study was to evaluate in a murine animal model the effect of SIS/Ch hydrogels in deep wound re-epithelialization. The SIS/Ch hydrogels were also evaluated in-vivo in a murine model with excisional full thickness wound, including the panniculus carnosus (n=6, 21 days). Carboxymethylcellulose hydrofiber and open wound were used as positive and negative controls, respectively. Wound contraction, histology and immunohistochemical analysis were performed...